Being a doctor in Brazil in the conception of Medical students (Research, Society and Development, 2020)
Objective: To know the perception of medical students about what it is to be a doctor in Brazil. Method: Qualitative study through semi-structured interviews with students from the basic, clinical and boarding cycles of a public educational institution. The interview script answered in writing contained sociodemographic data and an open question about what it is like to be a doctor today in Brazil. Content analysis of the textual data was performed, with the support of the webQDA software. Results: 210 students participated, 107 female and 103 male, with 70 from the basic cycle (first period), 83 from the clinical cycle (fourth and ninth periods) and 42 from the boarding school (twelfth period). The textual data gave rise to three categories: conception of what it means to be a doctor; challenges of medical practice; and suffering from the learning and exercise of Medicine. In each category, differences in students' perceptions were observed as they progressed through the course. The conception of what it means to be a doctor in the basic cycle is close to the profile of the graduate recommended by the National Curricular Guidelines and moves away from it in more advanced periods, as well as showing greater challenges in recent years and the more advanced the period, the more frequently the student suffering inherent in the educational environment and the practice of medicine. Conclusions: The perception of the respondents shows the disillusionment with what it is to be a doctor today in Brazil and the challenge of exercising the profession according to the profile of the graduate recommended in the National Curriculum Guidelines due to the barriers faced.